Comparison of Abrasiveness of Different Powders Used in Prophy-Jet - M - Ketabi; Sh Amini; S Jannatti Moheb (Isfahan University of Medical Sciences, 2005)
Introduction. Prophy-jet is a device which is used for removal of extrinsic stains and cleaning of implant surfaces. However, some reports showed that sodium bicarbonate used in prophyjet has abrasive effects. The aim of this research was to compare the abrasive effects of 3 different powders namely, Air flow (standard sodium-bicarbonate), Soda (not purified sodium bicarbonate- which is cheap and is used for polishing porcelain crowns) and (Jet fresh) aluminum trihydroxide.Materials and Methods. Sixty extracted teeth were divided in 3 equal groups. In first, second and third group, Air flow, Soda and Jet fresh were used as powder in prophy jet. Then slurry of prophyjet (EMS-piezone) was sprayed from 2 millimeters on each tooth surface for 60 seconds. Defects formed on tooth surfaces were measured under electron microscope.Results. Soda was less abrasive than standard Air flow and Jet fresh. Average cavity depths were 0.25, 1.33 and 1.75mm accordingly.Conclusion. Powders used in prophyjet could have abrasive effects. Soda may be safer to be used in prophyjet. However, due to its crystal sizes, it often causes blockage of prophyjet tubes.Key words. Propyhyjet, Airflow, Jetfresh, Abrasion.